Telling the stories of life through guided autobiography groups - Birren, James E. (Johns Hopkins University Press, 2001)
Annotation Telling the Stories of Life through Guided Autobiography Groups, based on James Birren's 25 years of conducting autobiography groups, discusses all the topics an organizer faces while developing a program for adults who want to recall and write down their life histories. This book is ideal for adult education programs, church groups, social workers, psychologists, gerontologists, and others who work with adults who might be interested in exploring, recording, or sharing their personal histories. It helps professionals and trained workshop leaders at community centers, senior centers, schools and other settings guide group participants in exploring major themes of their lives so that they can organize and write their stories and share them in a group with others on the same journey. This exercise is rewarding for adults of any age in a period of transition or with interest in gaining insight from their own stories. Personal development and a feeling of connection to other participants and their stories is a natural outcome of this process. This book provides background material and detailed lesson plans for those who wish to develop and lead an autobiography group. The authors explain the concept of guided autobiography, discuss the benefits to the group participants, and provide logistical information on how to plan, organize, and set up a group. An appendix provides exercises, handouts, and suggested adaptations for specific groups. The book also explains a systematic method of priming memories, including the history of family and of one's life work, the role of money, health and the body, and ideas about death. At a time when rapid change has created a widespread yearning to write down and exchange personal accounts, sharing life stories can reveal a great deal about how we have come to be the persons we are. Telling the Stories of Life through Guided Autobiography Groups shows how to organize, record, and share life experiences through a proven and effective technique.